Characterization of Southeast Asia mangoes (Mangifera indica L) according to their physicochemical attributes - Lawson, Tamunonengiyeofori; Lycett, Grantley W.; Ali, Asgar; Chin, Chiew Foan (Elsevier, 2019)
Mango (Mangifera indica L.) is an economically important fruit crop grown in the tropics. One of the important traits of mango for successful commercial production is the storage quality of the fruit. This study was conducted to evaluate the postharvest qualities of three mango (Mangifera indica) varieties namely ‘Chokanan’, ‘Golden phoenix’ and ‘Water lily’ grown in Southeast Asia regions. The study found that variety and ripening stage had an impact on the postharvest qualities. In general, an increase in weight loss, L* value and soluble solids concentration (SSC) along with a reduction in titratable acidity (TA), firmness and hue value as ripening progressed were observed irrespective of the variety. Analysis of variance and multivariate analysis were used to characterize the ripening process. This study provides useful information for devising strategies in postharvest handling and implementation of breeding programs for mango crop improvement.